Effects of the tailored intervention program in lowering blood glucose levels and diabetes distress among patients with diabetes in Indonesia: a randomized controlled trial - Pranata, Satriya; Wu, Shu-Fang Vivienne; Wang, Tsae-Jyy Tiffany; Liang, Shu-Yuan; Bistara, Difran Nobel; Chuang, Yeu-Hui; Lu, Kuo-Cheng; Vranada, Aric (Jurnal Ners, 2023)
Introduction: Blood glucose levels and diabetes distress are the foremost factors contributing to diabetes treatment outcomes and managements. No tailored intervention program was implemented for patients with diabetes in Indonesia. This study aimed to investigate the effectiveness of a tailored intervention program in lowering blood glucose levels and diabetes distress among patients with diabetes patients in Indonesia. Methods: A randomized controlled trial (RCT) with pre-test and post-tests was applied. A total of 163 people with diabetes were collected for both intervention (n=80) and control (n=83) groups: A diabetes-tailored intervention program was attempted in the intervention group. Descriptive statistics, Analysis of Variant (ANOVA) and inferential statistics were used to analyze the data (significance level <0.05). Results: The mean blood glucose levels and diabetes distress before and after in the intervention group were 255.19 mg/dl, and 245.60 mg/dl (p-value >0.05); 2.46 and 2.01 (p-value <0.01). While the control group's mean of blood glucose levels and diabetes distress before and after the intervention was were 227.81 mg/dl, and 245.94 mg/dl (pvalue <0.05); and 2.37 (p-value >0.05). Conclusions: The diabetes-tailored intervention program is effective on decreasing blood glucose levels and diabetes distress, and showed a significant result to diabetes distress.